2014
DOI: 10.1007/s11079-014-9315-y
|View full text |Cite
|
Sign up to set email alerts
|

Leading Indicators of Currency Crises: Are They the Same in Different Exchange Rate Regimes?

Abstract: We investigate whether leading indicators of currency crises differ across exchange rate regimes using data for 88 countries in the period 1981-2010. Our estimates suggest that in fixed exchange rate regimes external indicators, such as deviations of the real exchange rate from trend and the growth of international reserves, have the strongest predictive power. In contrast, in floating exchange rate regimes monetary policy and credibility indicators, such as domestic credit growth and inflation, are the best l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…The third generation models emphasise the role of banking system vulnerability and weaknesses in contributing to a higher probability of currency crisis occurrence. The indicators included from these models are interest rate spread with an expected positive sign (Bajona and Peng, 2008; Zhao et al , 2014), current account with an expected negative sign (Emin and Aytac, 2016; Peltonen, 2006) and the US interest rate with an expected positive sign (Feridun, 2004; Flood et al , 2010).…”
Section: Datamentioning
confidence: 99%
“…The third generation models emphasise the role of banking system vulnerability and weaknesses in contributing to a higher probability of currency crisis occurrence. The indicators included from these models are interest rate spread with an expected positive sign (Bajona and Peng, 2008; Zhao et al , 2014), current account with an expected negative sign (Emin and Aytac, 2016; Peltonen, 2006) and the US interest rate with an expected positive sign (Feridun, 2004; Flood et al , 2010).…”
Section: Datamentioning
confidence: 99%
“…See for example, Schmidt and Zwick (2015), Ghosh et al (2014) and Fratzscher (2011). 28 See, for example, Joyce andNabar (2009), Furceri, Guichard andRusticelli (2012), and Zhao et al (2014).…”
Section: The Consequences Of Sudden Stopsmentioning
confidence: 99%
“…Studies have used a probit model to estimate the probability of currency crises or currency crashes (Eichengreen et al 1996: Frankel andBerg and Pattillo 1999;Kruger et al 2000;Komulainen and Lukkarila 2003;Frankel 2005;Licchetta 2011;Furceri et al 2012;Zhao et al 2014). 6 Before examining the empirical literature, it is worth distinguishing between "currency crises" and "currency crashes" because these are two different concepts that are frequently confused.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, according to the probit estimation results presented by Furceri et al (2012), international reserves and short-term interest rates are relevant for the probability of currency crashes. Zhao et al (2014) found that real exchange rate overvaluation and international reserves are important determinants of currency crashes for fixed exchange rate regimes, whereas credit growth is important for floating regimes.…”
Section: Literature Reviewmentioning
confidence: 99%